Socialization of the Visual Meaning of Basiba as a Cultural Identity Minangkabau to the Younger Generation through Digital Media: Sosialisasi Makna Visual Basiba sebagai Identitas Budaya Minangkabau kepada Generasi Muda melalui Media Digital - Sayuti, Muhammad; Melisa Suardi; Steffany; Okta Andrica Putra; Harkamsyah Andrianof (Journal of Community Service and Application of Science, 2025)
Basiba is an important element in traditional Minangkabau women's clothing, possessing profound philosophical value and reflecting local cultural identity. However, amidst globalization and the dominance of popular culture, the younger generation is beginning to lose touch with traditional cultural symbols, including Basiba. This community service project aims to disseminate the visual meaning of Basiba as a Minangkabau cultural identity to the younger generation through a digital media-based visual communication design approach. This topic was chosen based on the urgency of preserving local cultural values in a format relevant to media developments and the information consumption patterns of today's young generation. Partners in this activity are student and university students in Padang City who have a Minangkabau background but have minimal knowledge about the philosophy of traditional clothing. The community service method includes observation, focus group discussions (FGDs), creation of digital visual content (such as infographics, educational videos, and social media campaigns), and evaluation through questionnaire before and after the activity. The results showed an increased understanding and appreciation of the visual meaning of Basiba, as well as an increased interest in relearning other local cultural symbols. Digital media has proven effective in bridging cross-generational communication and rebuilding a lost cultural identity. This activity underscores the importance of visual strategies and digital technology in supporting the sustainable preservation of Minangkabau culture among the younger generation.